Evolution of surgical suture in case of repairing the damaged flexor tendons of the fingers - D. G. Nakonechnyi; A. N. Kiseleva (Вестник хирургии имени И.И. Грекова)
The review includes the analysis of the evolution of surgical suture in case of repairing the damaged flexor tendons of the fingers.